A stress-based charging protocol for silicon anode in lithium-ion battery: Theoretical and experimental studies. (December 2020) - Zhang, Kai; Zhang, Yuwei; Zhou, Junwu; Li, Yong; Zheng, Bailin; Yang, Fuqian; Kai, Yue
Highlights: Based on the stress analysis in a silicon particle, a feasible stress-based charging protocol for silicon-based lithium-ion batteries is developed. Applying a moderate cut-off voltage (600 mV in this work) can achieve high reversible capacity and good cycling performance. The stress-based charging protocol is validated for all C-rates tested in this work. Abstract: The large mechanical deformation induced by the lithiation/delithiation of silicon can induce rapid capacity fading of silicon-based lithium-ion battery. This work is focused on the development of a feasible stress-based charging protocol that can control the stress and deformation of silicon anode during electrochemical cycling from the stress analysis in a silicon particle. The stress-based charging protocol provides an approach to suppress the mechanical stress in silicon anode with the control of the upper cut-off voltage for delithiation. The numerical results reveal that applying a small upper cut-off voltage for delithiation can reduce the mechanical stress and lower the capacity of the silicon electrode, while it likely improves the performance of the silicon-based lithium-ion battery. Experimental study of silicon-based lithium-ion half cells reveals that applying a moderate cut-off voltage (600 mV in this work) achieves high reversible capacity and good cycling performance for all the C-rates tested in the work, and applying a large cut-off voltage of 1000 mV leads to the formation of large surface cracks and rapid capacity loss. The experimental results support the stress-based charging protocol, which is developed from the numerical analysis, that tuning the cut-off voltage can reduce the structural degradation and enhance the electrochemical performances of silicon-based lithium-ion battery.